Compartmentalisation of cAMP-dependent signalling in blood platelets: The role of lipid rafts and actin polymerisation. (June 2015) - Raslan, Zaher; Naseem, Khalid M.
Abstract Prostacyclin (PGI2) inhibits blood platelets through the activation of membrane adenylyl cyclases (ACs) and cyclic adenosine 3', 5'-monophosphate (cAMP)-mediated signalling. However, the molecular mechanism controlling cAMP signalling in blood platelet remains unclear, and in particular how individual isoforms of AC and protein kinase A (PKA) are coordinated to target distinct substrates in order to modulate platelet activation. In this study, we demonstrate that lipid rafts and the actin cytoskeleton may play a key role in regulating platelet responses to cAMP downstream of PGI2. Disruption of lipid rafts with methyl-beta-cyclodextrin (MβCD) increased platelet sensitivity to PGI2 and forskolin, a direct AC cyclase activator, resulting in greater inhibition of collagen-stimulated platelet aggregation. In contrast, platelet inhibition by the direct activator of PKA, 8-CPT-6-Phe-cAMP was unaffected by MβCD treatment. Consistent with the functional data, lipid raft disruption increased PGI2-stimulated cAMP formation and proximal PKA-mediated signalling events. Platelet inhibition, cAMP formation and phosphorylation of PKA substrates in response to PGI2 were also increased in the presence of cytochalasin D, indicating a role for actin cytoskeleton in signalling in response to PGI2. A potential role for lipid rafts in cAMP signalling is strengthened by our finding that a pool of ACV/VI and PKA was partitioned into lipid rafts. Our data demonstrate partial compartmentalisation of cAMP signalling machinery in platelets, where lipid rafts and the actin cytoskeleton regulate the inhibitory effects induced by PGI2. The increased platelet sensitivity to cAMP-elevating agents signalling upon raft and cytoskeleton disruption suggests that these compartments act to restrain basal cAMP signalling.